T axillus chinensis (DC.) Danser: a comprehensive review on botany, traditional uses, phytochemistry, pharmacology, and toxicology - Mi Qin; Qianqian Huang; Xin Yang; Lu Yu; Yong Tang; Chunxiang Zhang; Dalian Qin; Wenjun Zou; Junzhu Deng; Jian Liu; Haiyang Hu; Long Wang; et al. (Chinese Medicine, 2022)
Abstract Background Taxillus chinensis (DC.) Danser (T. chinensis), known as “Sangjisheng” in Chinese, is a member of the family Loranthaceae, with the traditional functions of “dispelling wind dampness, strengthening bones and muscles, and preventing miscarriage”. Since Eastern Han dynasty, it has been used for the treatment of rheumatoid arthritis, arthralgia, threatened abortion, and hypertension. Nowadays, T. chinensis is included in the 2020 Edition of the Chinese Pharmacopoeia as Taxilli Herba. The purpose of this review is to summarize the latest research on T. chinensis in recent years, and make critical comments, so as to provide reference for the clinical application and modern research of T. chinensis. Main body In this review, we summarize the botany, traditional uses, and research advances in the phytochemistry and pharmacological effects of T. chinensis. Its toxicity has also been discussed. The published literature on current pharmacological and toxicological data has also been assessed. To date, approximately 110 compounds, including flavonoids, phenolic acids, phenylpropanoids, tannins, glycosides, amino acids, and nucleosides, have been identified in T. chinensis. Flavonoids are considered the most vital bioactive ingredients in T. chinensis. Pharmacological studies have demonstrated that T. chinensis possesses anti-inflammatory, antioxidant, anticancer, antimicrobial, antiviral, diuretic, antihypertensive, antihyperglycemic, and other properties. Conclusion Currently, research on T. chinensis is in the preliminary stages, and further research is required to understand the active compounds present and mechanisms of action. We hope that this comprehensive review of T. chinensis will serve as a background for further research.